2004
DOI: 10.1111/j.0022-0477.2004.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spatial patterns of damping‐off disease and arbuscular mycorrhizal colonization on tree seedling establishment in Ghanaian tropical forest soil

Abstract: Summary1 Milicia regia (Moraceae) is a dioecious light-demanding (Pioneer) timber tree of West Africa. Experiments in shadehouses were used to examine the influence of light and soil source (beneath and away from conspecific adults) on mortality and growth of its seedlings in relation to fungal pathogens and arbuscular mycorrhizal (AM) colonization. 2 The experiment in Ghana included treatments for light (2% and 20% of unshaded irradiance), three soil sources (under female, under male and 200 m distant from ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(126 citation statements)
references
References 33 publications
13
110
0
3
Order By: Relevance
“…Moreover, fungal growth was not influenced by canopy cover (Fig. 3A) unlike other seed/seedling pathogens reported for which ''damping off '' effects are reduced by high light associated with gaps (Augspurger 1983, Hood et al 2004). Invertebrates may inadvertently facilitate spread and impact of this fungus on masting seed populations by creating entry points for infection.…”
Section: Seed Pathogensmentioning
confidence: 84%
“…Moreover, fungal growth was not influenced by canopy cover (Fig. 3A) unlike other seed/seedling pathogens reported for which ''damping off '' effects are reduced by high light associated with gaps (Augspurger 1983, Hood et al 2004). Invertebrates may inadvertently facilitate spread and impact of this fungus on masting seed populations by creating entry points for infection.…”
Section: Seed Pathogensmentioning
confidence: 84%
“…In our study, understory juveniles encountered a much more diverse suite of fungal symbionts than did their mature counterparts. This canopy-understory disconnection is important because although several studies have shown distance-dependent pathogen or mutualist patterns for soilborne organisms (Augspurger 1984, Newbery et al 2000, Hood et al 2004, to our knowledge none have yet demonstrated that the canopy serves as a reservoir for symbionts. Density of airborne fungal spores is many times lower in the rainforest canopy than the understory , probably reflecting both reduced colonization of canopy leaves and environmental conditions hostile to spore production.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have generally found that seedling survival and growth are reduced in soil collected near conspecific adults due to an accumulation of soil-borne fungal pathogens (Augspurger 1984, Packer and Clay 2000, Hood et al 2004, Bell et al 2006. Differences in seedling performance when grown in soils near and far from a conspecific adult tree may be of no surprise considering the large amount of time in which fungal pathogens are allowed to accumulate.…”
Section: Scale and Ecological Implicationsmentioning
confidence: 99%
“…For example, negative plant-soil feedback is a frequency-dependent process, which can result from the accumulation of detrimental organisms (e.g., plant pathogens) that have species-specific effects in soils surrounding adult plants. This buildup, in turn, can decrease the growth and survival of conspecific juveniles rooted in close proximity to their adults (Augspurger 1984, Bever 1994, Mills and Bever 1998, Packer and Clay 2000, Klironomos 2002, Hood et al 2004, Bell et al 2006, Petermann et al 2008. Consequently, diversity is maintained because juveniles of other plant species (i.e., heterospecifics) that are relatively less affected by these pathogens have a competitive advantage at these sites (Connell et al 1971, Bever 1999.…”
Section: Introductionmentioning
confidence: 99%